Genealogy and Epistemological Configuration of Malay Islam and Nusantara Islam in Contemporary Islamic Studies - Hendri Farozah; Syarkoni Syarkoni; Ris’an Rusli (JURNAL AT-TURAS, 2025)
This study analyses the conceptual genealogy of Malay Islam and Nusantara Islam and examines the similarities and differences between them in contemporary scientific discourse. Although the two terms are often used interchangeably in academic and public discourse, systematic studies comparing their historical foundations, epistemic actors, and conceptualisation processes are still limited. This gap is the main focus of this study. This study uses a library method with a historical-critical approach and conceptual analysis, which is operationalised through discourse tracing of historical and academic sources, as well as conceptual mapping of the construction of meaning of the two terms. The research data includes classical Malay manuscripts, works of Islamic philology and historiography, religious anthropology literature, and recent scientific publications in Islamic and Southeast Asian studies. The results of the analysis show that Malay Islam is rooted in a pre-modern Islamisation process that was institutionalised through a network of scholars, kingdoms, and classical literacy traditions, while Islam Nusantara is a modern discursive construction that has developed in an academic and religious organisational context since the early 21st century. This study identifies three main findings: similarities between the two in their accommodative and moderate orientation towards Islam; differences in their historical basis, cultural space, and discourse-forming actors; and the strategic role of both in formulating a contextual Islamic paradigm. Theoretically, this research contributes to strengthening the study of Islamic epistemology and Southeast Asian studies by offering a more precise comparative framework for understanding local Islam as a historical and discursive construct.